If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 7y + -2y + -6 Reorder the terms: 19 = -6 + 7y + -2y Combine like terms: 7y + -2y = 5y 19 = -6 + 5y Solving 19 = -6 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 19 + -5y = -6 + 5y + -5y Combine like terms: 5y + -5y = 0 19 + -5y = -6 + 0 19 + -5y = -6 Add '-19' to each side of the equation. 19 + -19 + -5y = -6 + -19 Combine like terms: 19 + -19 = 0 0 + -5y = -6 + -19 -5y = -6 + -19 Combine like terms: -6 + -19 = -25 -5y = -25 Divide each side by '-5'. y = 5 Simplifying y = 5
| 2(y-8)-6y=-32 | | 8t+t=11 | | 30+(180-(8+6x))+(4x+2)=180 | | C-0.12(0)=330 | | 26.75=3x+5s | | 6.1a+12=66.9 | | 60=2r | | 3(4-5x)=42 | | 16=2p | | 60=2 | | 6x+21=6x+21 | | 42900+(0.2x)=x | | 3x=64-5x | | 25x+1=76 | | 2x+3x+x+60=180 | | 9h-16=h-2(2-3h) | | 28+x^2-11x= | | 1a+12=66.9 | | 1a+12=66.8 | | 72=9xd | | -2k+5=21 | | 3y-6=-21 | | R^2+35=12 | | A=3ab | | =-32 | | -13+2x=39+8x | | 61=4x-15 | | 0.14x+0.9(x-2)=0.01(4x-2) | | -2b+1=-17 | | 17x-3=82 | | 13x+45=19x+3 | | 7g+14-39=6 |